MENINGKATKAN PERKEMBANGAN BAHASA INDONESIA ANAK USIA DINI MELALUI PENGGUNAAN METODE BERCERITA PADA KELOMPOK A DI TK MALAHAYATI NEUHEN TAHUN PELAJARAN 2015/2016 - Rusniah Rusniah (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
The development of language in the early childhood is the development of language that must be owned by the child as one of their basic skills, according to the stage of age and characteristics of its development. This research generally aims to improve verbal language, specifically to find out how big is the ability of spoken language through the application / use of storytelling method. This research conducted in class A TK (Kindergarten) Malahayati Neuheun for Education Year 2016/2017. The subjects of the study were 22 children, 6 male students and 16 female students. The data of this research are data of students` verbal language ability, Instrument of data collection with observation sheet and data collection technique with observation. Data analysis technique used comparative descriptive method that compares cycle I and cycle II respectively in two meetings. Based on the obtained data analysis, the learning activity used II cycles, as many as 4 meetings. In the first cycle of 1st meeting the number of presentations of 36.4% was continued with the 2nd meeting of 54.5%. While on the 2nd cycle of 68% meeting followed by the 2nd meeting to 86.4%, this enhancementhas exceeded the learning mastery. The results showed that the recurring storytelling method enable to train children's concentration in improving their language skills through listening and expressing the language in group A TK Malahayati Neuheun